2022
DOI: 10.1109/jphot.2022.3192449
|View full text |Cite
|
Sign up to set email alerts
|

Relaying System Based on Few-Mode EDFA for Space Division Multiplexing Wireless Optical Communication

Abstract: Relay assisted transmission can compensate atmospheric turbulence, improve transmission distance, and realize communication between non-linear targets in free space optical communication (FSO) system. Space division multiplexing (SDM) greatly improves the channel capacity of FSO system. This paper focuses on the relay assisted transmission oriented to SDM wireless optical communication system. We develop a dual-hop SDM FSO communication model with two spatial mode channels. At the relay, the received optical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…They used the generalized gamma distribution to model the propagation of OAM modes through atmospheric turbulent FSO channels and derived closed-form expressions for various performance metrics. Cui et al [189] focused on relay-assisted transmission in SDM wireless optical communication systems. They developed a dual-hop SDM FSO communication model and demonstrated that the BER of the dual-hop SDM system with a few-mode EDFA-based relay outperformed the single-hop SDM system.…”
Section: Sdm/oam For Fso-based Ntnmentioning
confidence: 99%
“…They used the generalized gamma distribution to model the propagation of OAM modes through atmospheric turbulent FSO channels and derived closed-form expressions for various performance metrics. Cui et al [189] focused on relay-assisted transmission in SDM wireless optical communication systems. They developed a dual-hop SDM FSO communication model and demonstrated that the BER of the dual-hop SDM system with a few-mode EDFA-based relay outperformed the single-hop SDM system.…”
Section: Sdm/oam For Fso-based Ntnmentioning
confidence: 99%
“…In (Raza et al, 2023), LG00 and LG01 modes were multiplexed to increase the system bandwidth using intensity modulation. In (Cui, Cai, and Zhang, 2022), 2-hop free space optics (FSO) transmission was established using LP01 and OAM+1 modes, facilitated by a few modes' fiber relays at 1550nm. In (Badavath et al, 2023), 3-bit depth grayscale images are transmitted on three LG beams through FSO and retrieved using a convolutional neural network on speckle distributions.…”
Section: Related Workmentioning
confidence: 99%